Development of international legal mechanisms to protect older people’s health rights - Kashina , Evgeniia; Bogdan , Varvara; Agarkov , Bogdan (Interacción y Perspectiva, 2023)
The article examines the international experience of the legal protection of the health of the elderly. The problem of maintaining and preserving the health of older persons, who represent a growing part of the world’s population, is becoming increasingly urgent but appears insufficiently researched in terms of the features of legal regulation. The purpose of the presented work is to find successful legal solutions on the problems of protecting the health of the elderly and to create a comprehensive framework of legal regulation of the protection of their rights. International legislation guaranteeing the protection of the health of this category of persons is studied, and the role and importance of relevant international legal regulations are demonstrated. The declarative and ambiguous nature of current international normative regulation is emphasized and the ways of its improvement are suggested. In particular, the authors conclude that with the development of sustainable development mechanisms, there will be more international-level mechanisms to regulate the protection of the rights of older people. This will ensure the harmonization of national legislation and the adoption of universal standards, close to those available in advanced countries in this field, along with supranational control. The development of international mechanisms should be particularly directed toward the possibility of holding violating states accountable through specialized socio-legal institutions and regulatory mechanisms.